Historical Science in Buryat-Mongolia, 1920s–1930s: Peculiarities of Formation Analyzed - Anna M. Plekhanova; Evgenii V. Nolev (Oriental Studies, 2022)
Goals. The article seeks to reveal specifics of historical science’s institutionalization in the Buryat-Mongol ASSR throughout the 1920s and 1930s. It analyzes the conditions to have accompanied the development of historical science in the prerevolutionary era, peculiarities in the shaping of new organizational forms for historical research in the Republic (scientific institution, scientific society, museums and archives), and a corresponding educational infrastructure. Much attention is paid to the analysis of history and ethnography research endeavors of scientific societies (Dorzhi Banzarov Buryat-Mongol Society, Troitskosavsk-Kyakhta Branch of the Russian Geographical Society) and the first scientific institution of the Republic to have evolved from Buryat-Mongol Scientific Committee into the State Institute of Language, Literature and Cultural History during the mentioned period. Materials and methods. The paper examines unpublished documents stored at the Center of Oriental Manuscripts and Xylographs (Institute for Mongolian, Buddhist and Tibetan Studies SB RAS), Scientific Archive of the Buryat Scientific Center (SB RAS), and the State Archive of Buryatia. The principles of historicism and systemacity employed make it possible to reconstruct the process of historical science’s institutionalization in the young Buryat-Mongol autonomy, the latter having been determined by objectives of scientific, cultural, social, economic and political development of the Soviet state. This has yielded a balanced approach aimed to characterize the ideological predicaments faced by the humanities in earliest decades of the BMASSR. Results. The first post-October decade witnessed the shaping of a conceptually new paradigm of historical science based on Marxist-Leninist ideologies — paralleled by the formation of Buryat-Mongolia’s infrastructure of historical science represented by institutions of science and education, public organizations and archives. In methodological terms, the very historical science was being developed ‘under the flag of local history’ with the typically insufficient detailing and generalizing nature of historical problem statements. The first 1926 meeting on ethnic culture and the 1934 meeting on controversial issues of Buryat-Mongolia’s history did articulate consolidated ideas pertaining to development directions and objectives for historical science in the Republic. Despite the ideological extremities had had most negative impacts on human resources and potentials of regional historical science, by the late 1930s there were a source base and theoretical/methodological tools generally compliant with Marxist-Leninist ideologies. All that helped P. Khaptaev, A. Okladnikov, F. Kudryavtsev and many others prepare generalized works on the history of Buryatia that have become classics of Russian historiography.